Proteomics Identification and Validation of Desmocollin‐1 and Catechol‐O‐Methyltransferase as Proteins Associated with Breast Cancer Cell Migration and Metastasis. Issue 21 (28th October 2019) - Faktor, Jakub; Knopfova, Lucia; Lapcik, Petr; Janacova, Lucia; Paralova, Vendula; Bouchalova, Pavla; Muller, Petr; Benes, Petr; Bouchal, Pavel
Abstract: Biological treatment of many cancers currently targets membrane bound receptors located on a cell surface. To identify novel membrane proteins associated with migration and metastasis of breast cancer cells, a more migrating subpopulation of MDA‐MB‐231 breast cancer cell line is selected and characterized. A high‐resolution quantitative mass spectrometry with SILAC labeling is applied to analyze their surfaceome and it is compared with that of parental MDA‐MB‐231 cells. Among 824 identified proteins (FDR < 0.01), 128 differentially abundant cell surface proteins with at least one transmembrane domain are found. Of these, i) desmocollin‐1 (DSC1) is validated as a protein connected with lymph node status of luminal A breast cancer, tumor grade, and Her‐2 status by immunohistochemistry in the set of 96 primary breast tumors, and ii) catechol‐O‐methyltransferase is successfully verified as a protein associated with lymph node metastasis of triple negative breast cancer as well as with tumor grade by targeted data extraction from the SWATH‐MS data of the same set of tissues. The findings indicate importance of both proteins for breast cancer development and metastasis and highlight the potential of biomarker validation strategy via targeted data extraction from SWATH‐MS datasets.